Ex-Post evaluation of the second pilot of the Index-Based Flood Insurance in Bihar, India: Reflections for upscale - Aheeyar, Mohamed M. M.; de Silva, Sanjiv; Senaratna Sellamuttu, Sonali (CGIAR Research Program on Water, Land and Ecosystems, 2020)
The major objectives of the evaluation were to understand the performance of the IBFI product in reaching diverse groups of farmers and the hindrances to making the insurance more inclusive, in order to recommend solutions and strategies to address equity issues.